2021
DOI: 10.1021/acs.organomet.1c00151
|View full text |Cite
|
Sign up to set email alerts
|

Homoleptic Cobalt(II) Phenoxyimine Complexes for Hydrosilylation of Aldehydes and Ketones without Base Activation of Cobalt(II)

Abstract: Air-stable, easy to prepare, homoleptic cobalt­(II) complexes bearing pendant-modified phenoxyimine ligands were synthesized and determined. The complexes exhibited high catalytic performance for reducing aldehydes and ketones via catalytic hydrosilylation, where a hydrosilane and a catalytic amount of the cobalt­(II) complex were added under base-free conditions. The reaction proceeded even in the presence of excess water, and excellent functional-group tolerance was observed. Subsequent hydrolysis gave the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…The experiments conducted are in favor of a classical mechanism involving a cobalt‐hydride as the active catalyst. In our case as for others [26c,27a,f,i,j] the hydrosilylation catalytic reaction works without any hydride additive, therefore the formation of the active Co−H species may result from σ‐bonds interchange at the metal center by the so‐called sigma‐bond metathesis [34] . Coordination of the ketone and its insertion into the Co−H bond leads to an alkoxo complex which upon reaction with the silane regenerates the active Co−H complex and releases the silyl ether (Scheme 5).…”
Section: Resultsmentioning
confidence: 95%
“…The experiments conducted are in favor of a classical mechanism involving a cobalt‐hydride as the active catalyst. In our case as for others [26c,27a,f,i,j] the hydrosilylation catalytic reaction works without any hydride additive, therefore the formation of the active Co−H species may result from σ‐bonds interchange at the metal center by the so‐called sigma‐bond metathesis [34] . Coordination of the ketone and its insertion into the Co−H bond leads to an alkoxo complex which upon reaction with the silane regenerates the active Co−H complex and releases the silyl ether (Scheme 5).…”
Section: Resultsmentioning
confidence: 95%
“…15 It was reported that phenoxyimine cobalt( ii ) complexes exhibited high catalytic performance for reducing aldehydes and ketones with silane as a reducing agent. 16 In 2020, Guan published that cobalt [POCOP] pincer complexes were catalysts for the hydrosilylation of aldehydes bearing various functional groups. 17 Most recently, cobalt complexes supported by phosphinoquinoline ligands were reported with high catalytic activity for the hydrosilylation of various ketones under mild conditions by Auffrant and Gosmini.…”
Section: Introductionmentioning
confidence: 99%
“…In consequence, the development of homogeneous catalysts based on EAMs has undergone remarkable revitalization over the last decade. 4 Among them, cobalt catalysts have shown excellent performances in a broad variety of reactions, 5 for example, in the reduction of organic substrates via hydrogenation, 6 transfer hydrogenation, 7 hydrosilylation, 8,9 reductive amination 10 or hydroboration. 11…”
Section: Introductionmentioning
confidence: 99%
“…19 However, examples of the cobalt-catalyzed reductive amination of carbonyl compounds employing hydrosilanes as reducing agents are scarce. 10 In fact, homogeneous cobalt catalysts have been extensively explored in the hydrosilylation of alkenes, alkynes and, to a lesser extent, carbonyl compounds; 9 however, imines have been widely overlooked. 20 An interesting example of the reductive amination of carbonyl compounds promoted by homogeneous cobalt catalysts has been reported by Beller and Jagadeesh.…”
Section: Introductionmentioning
confidence: 99%